Sustainability indicators for evaluation of municipal urban water management system: the case of Volta Redonda – RJ/Brazil - Garcez-de-Oliveira, Valéria; César, Aldara da Silva; Carrara, Ozanan Vicente; Mozer, Thiago Simonato (Desenvolvimento e Meio Ambiente, 2022)
The risks of scarcity have forced several countries to change their water resources management. In Brazil, the Paraíba do Sul River has a great importance as it supplies water for many cities of the Southeast region. Thus, the management of water and wastewater systems demands a more sustainable and efficient scenario. The study’s objective was to evaluate, through sustainability indicators, the urban water management system in Volta Redonda (Rio de Janeiro state, Brazil). The selection of sustainability indicators was done through Delphi technique: a group of eight specialists selected the indicators used to evaluate sustainability, its dimension and level of importance. The six criteria for the classification of indicators according to the dimensions of sustainability were: (1) Environmental / Ecological, (2) Economic, (3) Social / Cultural, (4) Technological (5) Ethical and (6) Political / Institutional. Most of the indicators were considered "very important" or just "important". Regarding the dimension of sustainability, 93% of indicators contemplated more than three dimensions. However, 13 indicators contemplated all the six dimensions as they were multidimensional indicators, analyzed according to the municipal data. The chosen method for the indicator’s selection was considered quite satisfactory, since they were able to generate a set of key indicators to show the current municipal water and wastewater scenario. The city has shown satisfactory conditions regarding fresh water supply index. However, some indicators pointed a not sustainable system due to the low wastewater treatment index, precarious state of the river’s life and divergences between the basin plan and the municipal director plan.